Adhesive bond dynamics in contacts between T lymphocytes and glass-supported planar bilayers reconstituted with the immunoglobulin-related adhesion molecule CD58. - Dustin, M (1997)
The interaction of the T cell glycoprotein CD2 and its ligand CD58 is important for T cell interaction with antigen-presenting and target cells. The binding interaction is of low affinity and has a fast off-rate (>5 s-1) in solution. However, solution measurements may not accurately predict the behavior of molecules in an adhesive contact area. Interaction between T cells that express CD2 and glass-supported planar bilayers containing purified and fluorescently labeled CD58 leads to accumulation of CD58 (fluorescence) in the cell/bilayer contact area. CD58 molecules accumulated within the contact area in excess of the CD58 density in the bilayer outside the contact area can be considered as bound by cell surface CD2. Here, this phenomena and fluorescence photobleaching recovery were utilized to determine whether CD2-CD58 bonds are transient in contact areas. Fluorescent CD58 molecules accumulated in the T cell-bilayer interface were completely bleached. The bleached CD58 molecules accumulated in the contact area were rapidly replaced by fluorescent CD58 that diffused into the contact area from adjacent bilayer regions outside the contact area. Rapid recovery of the accumulated fluorescence directly demonstrates that the CD2-CD58 bonds are dissociating and that the dissociation leads to partner exchange, rather than rebinding of the same CD2-CD58 pairs. This suggests that the solution off-rate provides an accurate description of CD2-CD58 interaction in contact areas. Accumulated fluorescent IgG in contacts between K562 cells expressing low affinity Fc receptors and planar bilayers with fluorescent IgG bound to hapten-derivitized phospholipids displayed slower recovery than CD58 by a factor of 10. This suggests that the Fc receptor-IgG interaction has a longer lifetime than the CD2-CD58 interaction. These findings have implications for the mechanism of signaling by CD2 and the mechanism of cell detachment from large numbers of transient interactions.